03 Volunteers – sustaining hospices?. (1st October 2013) - Scott, Ros
Abstract : Volunteers have historically played a vital role in the founding and on-going development of independent hospices. The governance of these voluntary organisations is also the responsibility of volunteer trustees, however, it is not clear whether volunteering is considered as strategic resource. This study aimed to explore how volunteering perceived strategically in independent hospices throughout the UK. Purpose of the Research The purpose of this research was to study the link between volunteering and hospice sustainability by: Exploring how volunteering is understood by UK hospice senior staff, volunteers and trustees. Considering the influence of volunteers on four key UK hospice sustainability factors: governance; service delivery; hospice economy; and community engagement. Explore whether there is a link between volunteering and hospice sustainability. Methods: Using a mixed methods approach a self-administered online survey which was sent to hospices across the UK. The questionnaire included both Likert Scale and free text questions. As this study sought to the strategic context of volunteering, the views of senior staff, trustees and volunteers were sought. Thirty one hospices took part with responses from 58 senior staff 56 trustees and 181 volunteers. Findings: No recognition of the role of volunteers in governance. Volunteers viewed as a strategic resource but not engaged in strategy development. Lack of planning for volunteer involvement. Volunteers are important to income generation, the quality and range of services offered and community engagement. Hospice sustainability is highly dependent on volunteers, however Current volunteering models may not be sustainable. Implications: This area is the first study of its kind to establish evidence about the dependence of hospices on volunteers. It identifies opportunities for practice development in planning and approach. A toolkit is being developed to enable organisations to identify areas for development.